2022
DOI: 10.3390/vaccines10101629
|View full text |Cite
|
Sign up to set email alerts
|

Monkeypox Vaccine Hesitancy in French Men Having Sex with Men with PrEP or Living with HIV in France

Abstract: People with pre-exposure prophylaxis (PrEP) or living with HIV are a high-risk population for monkeypox virus (MPXV) infection. It is important to achieve high MPXV vaccination coverage rates in this group. This project used self-reporting to assess vaccine hesitancy for the smallpox vaccine and acceptance among men having sex with men with PrEP or living with HIV. In total, 52 (33.6%) participants among the 155 declared their hesitancy to be vaccinated against MPXV. Moreover, 20.7% patients with PrEP declared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 31 publications
4
43
1
Order By: Relevance
“…A total of 56.8% of MSM living with HIV in our study were willing to get the Mpox vaccine. Similar to our findings, 59.8% of MSM living with HIV in France indicated their acceptance towards Mpox vaccination [ 41 ]. Dukers-Muijrers and colleagues found that 81.5% of the MSM surveyed in the Netherlands were willing to receive an Mpox vaccine [ 42 ].…”
Section: Discussionsupporting
confidence: 90%
“…A total of 56.8% of MSM living with HIV in our study were willing to get the Mpox vaccine. Similar to our findings, 59.8% of MSM living with HIV in France indicated their acceptance towards Mpox vaccination [ 41 ]. Dukers-Muijrers and colleagues found that 81.5% of the MSM surveyed in the Netherlands were willing to receive an Mpox vaccine [ 42 ].…”
Section: Discussionsupporting
confidence: 90%
“…For example, MPOX vaccination can have an important role in the preventive efforts for high-risk groups, including HCWs [ 19 ]. Additionally, satisfactory knowledge and positive attitude towards MPOX vaccination can affect HCWs’ recommendation of the vaccine for other high-risk groups (e.g., men who have sex with men (MSM)) [ 28 , 40 ]. Specifically, and in the context of MPOX vaccination intention among the general public in the U.S., Winters et al reported that the most trusted sources of information regarding the outbreak were HCWs [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our results, only 33% of physicians in a recent study among Turkish physicians were reported to have good MPOX knowledge [ 60 ]. Addressing these knowledge gaps can be valuable, since HCWs have a key role in community education and preparedness for outbreak response, particularly among high-risk groups (e.g., MSM and people living with HIV infections/AIDS (PLWHA)) [ 40 ]. This includes educational efforts necessary to recognize unusual presentation of the disease, including its genital manifestations [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al ( 123 ), showed that MSM using chemsex recently were less likely to perceive higher concern for MPXV infection ( 123 ). One of the explanations could be that MSM using chemsex tend to underestimate the STI risk in general ( 124 , 125 ). However, Thornhill et al ( 20 ), reported a prevalence of 20% of chemsex use among 528 infections diagnosed in 16 countries ( 20 ).…”
Section: Resultsmentioning
confidence: 99%